Using Frangenheim’s Thinking Skills Framework to Improve Academic Writing Skills in Tertiary ESL Classrooms - Beh Min Er; Malini Ganapathy (The English Teacher, 2021)
Malaysian undergraduates have been facing writing difficulties as a result of lacking effective guidance tools in upskilling English writing and activating thinking skills. Failing to achieve writing competency, the problems extend to the high unemployment rate among fresh graduates. This paper proposes using Frangenheim’s Thinking Skills Framework (TSF) to improve university students’ academic writing proficiency. 60 students were selected to undergo a 6-week quasi- experiment to investigate the effectiveness of the TSF on academic writing and focus group discussions were held to explore students’ perceptions on utilizing the TSF in writing processes. The results of the study confirmed the positive effect of using the TSF in improving students’ academic writing and promoting the use of Higher-Order Thinking Skills (HOTS) throughout the writing process. Findings revealed students’ perceptions on the TSF: an effective guidance tool with various writing strategies, comprises clues to activate suitable thinking skills, and assists writers’ idea generation and decision-making. The implications are important to tertiary stakeholders as a practical TSF is recommended as a supplementary tool to be infused in English writing syllabus to facilitate students in fulfilling the essential thinking skills and writing needs in higher education.